SAR simulations for high‐field MRI: How much detail, effort, and accuracy is needed?. Issue 4 (18th May 2012) - Wolf, S.; Diehl, D.; Gebhardt, M.; Mallow, J.; Speck, O.
<x xml:space="preserve">Abstract</x> Accurate prediction of specific absorption rate (SAR) for high field MRI is necessary to best exploit its potential and guarantee safe operation. To reduce the effort (time, complexity) of SAR simulations while maintaining robust results, the minimum requirements for the creation (segmentation, labeling) of human models and methods to reduce the time for SAR calculations for 7 Tesla MR‐imaging are evaluated. The geometric extent of the model required for realistic head‐simulations and the number of tissue types sufficient to form a reliable but simplified model of the human body are studied. Two models (male and female) of the virtual family are analyzed. Additionally, their position within the head‐coil is taken into account. Furthermore, the effects of retuning the coils to different load conditions and the influence of a large bore radiofrequency‐shield have been examined. The calculation time for SAR simulations in the head can be reduced by 50% without significant error for smaller model extent and simplified tissue structure outside the coil. Likewise, the model generation can be accelerated by reducing the number of tissue types. Local SAR can vary up to 14% due to position alone. This must be considered and sets a limit for SAR prediction accuracy. All these results are comparable between the two body models tested. Magn Reson Med 69:1157–1168, 2013. © 2012 Wiley Periodicals, Inc.